ANALISIS PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SHAMPOO SUNSILK BLACK SHINE MELALUI PERSEPSI KUALITAS SEBAGAI VARIABEL INTERVENING - Lestari, Ovy Dwi Putri; Handayani, Tati (Ekonomi dan Bisnis, 2016)
This research is a quantitative research that aims to determine the effect of brand image and price of the purchasing decision shampoo Sunsilk Black Shine through the perception of quality as an intervening variable. In this study sampels used were 100 respondents. Sampling technique using non - probability sampling with purposive sampling technique. Testing the hypothesis in this study using Path Analysis with SPSS 21. The results of this test coefficient of direct influence brand image on perceived quality is 0,531 or 53.1% , the coefficient of direct influence price on perceived quality is 0.292 or 29.2%, the coefficient of direct influence brand image on purchasing decisions by 0,243 or 24.3%, the coefficient of direct influence price on purchase decisions is 0.209 or 20.9% , the coefficient of direct influence perceive quality on purchase decisions by 0.476 or 47.6%. While the coefficient indirect influence brand image on purchase decisions through the perceived quality is 0.252 or 25.2%, and the coefficient of indirect influence price on purchase decisions through the perceived quality is 0.138 or 13.8%. Therefore, the coefficient of indirect influence is smaller than the coefficient of direct influence, it can be concluded that the effect is actually a direct influence.